2016
DOI: 10.4172/2471-9846.1000120
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Vitamin D and its Deficiency in Jeddah Population, Saudi Arabia

Abstract: Introduction: Vitamin D deficiency considered to be the most common nutritional deficiency and one of the most common undiagnosed medical conditions in the world. It appears to be a widespread global problem prevalent in all age groups, with a reported prevalence of 30-80% in children and adults This significant decreased in vitamin D level worldwide in different age group shows lack of awareness about vitamin D importance and its resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…24 In Jeddan population 65.5% recognised work or weather issues as major cause of inadequate exposure to sun. 25 Similar to our study, a survey in Poland showed that the most frequently mentioned sources of vitamin D was dairy products and mistaken responses were dominated by fruits and vegetables.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…24 In Jeddan population 65.5% recognised work or weather issues as major cause of inadequate exposure to sun. 25 Similar to our study, a survey in Poland showed that the most frequently mentioned sources of vitamin D was dairy products and mistaken responses were dominated by fruits and vegetables.…”
Section: Discussionsupporting
confidence: 86%
“…But source of information about vitamin D varied as compared to our study. 24,25 In Saudi, only 50% of patients were aware of heath implication of vitamin D. 20 66.8% of our participants also was unaware of any symptoms of vitamin D deficiency. In Zadka et al's study the respondents mostly declared vitamin D property as structure of bones and teeth (66%) and the report corresponds to our result as our respondents also only mentioned bone symptoms for vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 81%
“…This study provides insight regarding the current knowledge of the importance of vitamin D and attitudes toward sun exposure among premenopausal women attending the primary care clinic in Jeddah. Overall, it seems that women in Jeddah are more aware of vitamin D than those reported in the published literature [ 22 , 40 , 41 ]; for example, almost 99% of the women in the current study had heard of vitamin D, compared to 90% of parents of children ( n = 1752) in Jeddah [ 42 ] and 63% of the men and women ( n = 503, age 20–40 years old) in Sharjah, United Arab Emirates [ 40 ]. In comparison, one internationally published report stated that 73% of Chinese middle aged and elderly men and women ( n = 547) had heard about vitamin D [ 22 ].…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, Al-Agha's study showed a good level of knowledge about sun exposure and dietary intake as vitamin D sources, but many people had poor knowledge about the safe times for sun exposure and many did not have time due to their working lifestyle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in a French study that included a higher monthly income as a predictor [ 27 ]. While in Al-Agha's study, the low level of knowledge was not associated with education level [ 26 ], and in a United Kingdom study, older people showed a low level of knowledge [ 2 ].…”
Section: Discussionmentioning
confidence: 99%